“EXAMINING THE EFFECT OF KETO DIETS ON WEIGHT LOSS: THE QUALITATIVE STUDY OF EXPERIENCES AND PERCEPTIONS OF OBESE INDIVIDUALS” (Contemporary Journal of Social Science Review, 2025)
In recent years, the ketogenic diet has gained immense popularity worldwide. This diet emphasizes the consumption of high amounts of fat, moderate protein, and very few carbohydrates. The purpose of this research paper is to explore how the ketogenic diet affects our bodies, its effectiveness in treating neurological diseases, and its role in weight loss. Another objective was to investigate how the ketogenic diet promotes ketogenesis, which is beneficial for specific neurological conditions.As carbohydrate intake decreases, body weight is also expected to drop. Data was gathered from fifteen participants, including males and females, and a nutritionist, all from Islamabad. The research employed a qualitative explanatory study using purposive sampling for keto diet followers and convenient sampling for nutritionists. Data was collected through semi-structured interviews and questionnaires to gather insights into their experiences. The results indicated that participants experienced weight loss over 12 weeks and significant health improvements. The ketogenic diet showed more substantial short-term results compared to long-term observations. Studies revealed that the diet contributed to weight loss, improved blood sugar levels, reduced inflammation, and increased energy levels. The findings revealed that some challenges faced with prolonged adherence to the diet could lead to serious health complications, such as liver damage, kidney stones, and nutrient deficiencies. Further research is necessary to understand the long-term effects of the ketogenic diet on overall health and disease management.